(untitled) (Proceedings of International Conference on Special Education, 2023)
The purpose of this research is to document the legal transition of a developing island nation, namely Maldives, to establish a nation-wide inclusive education system that caters to all students, including those with special needs. The study sheds light on the significant milestones achieved, current status of implementation of the legislations, and suggests a roadmap towards achieving inclusion in schools. The investigation draws heavily on the relevant legal, policy, and other local documents to elicit the story on the legal domain. Data from reports and similar documents are used for examining the status of implementation. Major milestones and transitions that took place over the three and half decades in the inclusive education journey of the country are discussed in the paper. These milestones in implementation are cross-checked against the expectations stipulated in the relevant legislations. The study offers recommendations to improve and widen the scope of inclusive education in the country which could be lessons for countries similar in context.